Histopathological Evaluation of Prostatic Lesions, PSA Correlation And Use of P63 In Prostatic Adenocarcinoma Mimickers - Pariyar, Sanjib; Karki, Shovana; Sharma, Nisha (Journal of Bharatpur Hospital, 2025)
Background Prostatic lesions are common disorders causing morbidity and mortality among the elderly population. Benign prostatic hyperplasia (BPH) and prostatic adenocarcinoma are the common pathologies of prostate. Prostate specific antigen (PSA) and histopathological examination are important for diagnosis and management of prostatic adenocarcinoma. Prostatic adenocarcinoma mimickers may be difficult to diagnose for which p63 immunostaining is helpful in differentiating them from adenocarcinoma.MethodsIt was a hospital-based cross-sectional study conducted over one year period in the Department of Pathology, TUTH. Demography, procedure type, PSA levels, histopathological diagnosis and immunohistochemistry findings for suspected adenocarcinoma mimickers were collected and analyzed. ResultsA total of 123 cases of prostatic lesions were enrolled, out of which 74% were benign and 26% were malignant. The most common age group was 61-70 years for both types of lesion. The median PSA values for benign and malignant prostatic lesions were 3.21 and 33.55 ng/mL respectively and the difference was statistically significant. The commonest Gleason system score in prostatic adenocarcinoma cases was score 9 (43.8%) with predominant pattern being pattern 4. Similarly, the most common grade group was grade group 5 (46.9%). The commonest histopathological diagnosis was BPH (59.3%), followed by adenocarcinoma (26%). Immunohistochemistry, p63 was performed in 18 suspected prostatic adenocarcinoma mimicker cases, among which 5 cases were positive.Conclusions PSA is a sensitive tumor marker, helpful in diagnosis of prostatic cancer. However, histopathology remains the gold standard for the diagnosis of prostatic carcinoma. Immunohistochemistry, p63 plays an important role in differentiating prostatic adenocarcinoma mimickers from adenocarcinoma.